IMPLEMENTASI PERAN KEPALA SEKOLAH DALAM MEMBENTUK KARAKTER MANDIRI SISWA DI KB CERIA DANAWANGSA SITANGGAL BREBES - Ayang Mutiara Kasih Suci; Suyadi (ICO EDUSHA, 2022)
Covid-19 has had a negative impact on various aspects, especially on the economic structure of micro, small and medium enterprises (UMKM). The Indonesian government has launched a national economic recovery program to deal with the economic crisis due to the covid-19 pandemic, namely the bpum program which is aimed at micro-enterprises affected by the pandemic. the purpose of this study was to determine the effectiveness of receiving business capital assistance for micro business actors (BPUM) in maintaining msmes during the covid-19 pandemic (analysis study of micro business actors in pamulihan village, larangan district, brebes regency). this research uses descriptive qualitative methods. the data collection techniques used are interviews, observation and documentation studies. Respondents in this study were Muslim micro-enterprises in the Brebes area who received BPUM in 2020 and 2021, totaling 17 people. The results of the study show the effectiveness of receiving business capital assistance for micro business actors (BPUM) in maintaining UMKM during the covid-19 pandemic in Pamulihan Village, Kec. District Ban. Brebes as a whole has not been effective in its implementation based on indicators of effectiveness according to Budiani, namely, effective in terms of indicators of program target accuracy, program socialization and achievement of program objectives, but from the monitoring indicators for the Assistance for Micro Business Actors (BPUM) program it has not been effective because in the process of receiving BPUM afterwards it was not there is a monitoring process from the department and related parties. Keywords: BPUM, Effectiveness, Covid-19 Pandemic, UMKM. References Ahmad Mushthofa, dkk. 2022. “Peran Kepala Sekolah dalam Pengembangan Karakter Siswa Berbasis Profesionalisme Guru,” Southeast Asian Journal of Islamic Education Management 3, no. 1 hlm. 35–44, diakses melalui https://doi.org/10.21154/sajiem.v3i1.81. Loeziana Uce, The Golden Age : Masa Efektif Merancang Kualitas Anak, Pusat Jurnal UIN Ar-Raniri (Universitas Islam Negeri), diakses melalui 228450173.pdf (core.ac.uk) Moleong, Lexy J. 2017. Metode Penelitian Kualitatif. Bandung : PT. Remaja Rosdakarya Offset Mulyadi. 2015. Perilaku Organisasi dan Kepemimpinan Pelayanan. Bandung: Alfbeta Mushthofa, dkk. “Peran Kepala Sekolah dalam Pengembangan Karakter Siswa Berbasis Profesionalisme Guru.”. hlm. 40 Purwanto, M. Ngalim. 2012. Administrasi dan supervise Pendidikan. Bandung: Rosda. hlm. 14 Saleh, dkk. “Peran Kepala Sekolah Sebagai Administrator Dalam Meningkatkan Efektivitas Layanan Administrasi Di Smp Santu Petrus Pontianak.” Sudaryanti. 2015. “Pentingnya Pendidikan Karakterbagi Anak Usia Dini,”Jurnal Pendidikan Anak 1. diakses melalui https://doi.org/10.21831/jpa.v1i1.2902. Sugiyono. 2016. Metode Penelitian Pendidikan, Bandung : Alfabeta. hlm. 338 Sugiyono. 2018. Metode Penelitian Kuantitatif. Bandung: Alfabeta. hlm 247-249 Sugiyono. 2018. Metode Penelitian Kuantitatif. Bandung: Alfabeta. hlm 252-253 Yesi Saputri dan Nim Tk. 2020 “Prodi Manajemen Pendidikan Islam Fakultas Tarbiyah Dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi 2020,”. hlm. 104.